478 Injuries in children with autism spectrum disorder: study to explore early development (SEED). (1st September 2016) - DiGuiseppi, Carolyn; Levy, Susan; Soke, Gnakub N; Rosenberg, Steven; Sabourin, Katherine R; Lee, Li-Ching; Moody, Eric; Schieve, Laura
Abstract : Background: Studies of injury risk in children with autism spectrum disorder (ASD) have shown conflicting results. We examined medically-treated injuries in children with ASD vs. population (POP) controls. Methods: The Study to Explore Early Development (SEED) is a multi-site ASD case-control study of children aged 30–68 months. ASD cases (n = 693) were determined using established ASD-specific diagnostic instruments. POP controls (n = 882) were ascertained from birth certificates. Each child's primary caregiver reported if the child ever had a medically-treated injury and described each such injury. Injuries resulting in emergency department visit or hospitalisation were defined as "serious." We describe the nature and cause of each child's first reported injury. Associations between ASD and having at least one medically-treated injury and serious injury were examined using logistic regression, adjusted for child sex, age, and IQ; maternal race/ethnicity and education; and family income. Results: Among children with ASD, 33% ever had a medically-treated injury and 25% ever had a serious injury; the most commonly specified injuries were laceration (41%), fracture (22%) and abrasion/contusion (12%). Among POP children, 30% had a medically-treated injury and 22% a serious injury; the most commonly specified injuries were laceration (46%), fracture (23%) and dislocation/sprain (12%). In both groups, the cause most often specified was a fall (56%). ASD cases and POP controls had similar odds of injury (crude odds ratio [cOR] = 1.1 [95% CI: 0.9, 1.4]; adjusted OR [aOR] = 1.2 [0.9, 1.7]) and serious injury (cOR = 1.1 [0.9, 1.4]; aOR = 1.2 [0.9, 1.6]). Conclusions: Children with ASD and population control children had similar odds of any medically-treated injury and serious injury. Sociodemographic and IQ differences did not influence these results. We plan to further explore and compare specific injury types and causes, and additional injury outcomes, between the two groups.